Observations regarding the lexical content at the beginnings of structural semantics - Dinu Moscal (Diacronia, 2019)
This study focuses on the difficulties noted by a series of German lexicologists at the beginnings of structural semantics as part of their attempt to identify a possible method of organizing the lexis of a language. Their studies, beginning with Jost Trier, focused on the analysis of certain lexical groups called Wortfelder (“lexical fields”), regarded as parts of a completely organized lexis. Their idealistic perception—according to which the whole lexis of a language has an inner organization that needs to be discovered—was confronted with some major issues. Our first observation, based on some examples from the lexis, reveals the fact that certain words cannot be classified as belonging to a specific lexical field. Another observation is related to the semantic continuum of the lexical field, which is compared in some works with the image of a mosaic. These issues are detailed by the argumentations of the German lexicologists, whose research was based on a diachronic analysis of the lexis. Their views were exploited in the second stage of the theorization of lexical fields.